Arquitetura da informação e estresse digital no contexto das mídias sociais digitais - Madruga, Tanise Dantas Bezerra (2024)
Immersing in the fatigue society, especially during the COVID-19 pandemic and post-pandemic time, this Thesis reflected on the relational aspects of Information Architecture and Digital Stress in the context of Digital Social Media. In these liquid times, typical of digital culture, the subject of performance submitted to an excess of positivities compulsorily experiences a coercive freedom expressed by criativity, performance, innovation, individual and flexible initiatives, in a context in which the excess of labor and performance intensifies in a self-exploitation. In effect, this is a consequence of the incessant search for the hyperconsumption of information in digital environments, in line with the repercussions of the digital technological revolution, which makes technology an intermediary for various socio-cognitive processes. In this regard, it was observed that research about information and health is a trend in the Information Science field. During the research, it was questioned how the Information Architecture of Digital Social Media influences Digital Stress in people, based on the hypothesis that an Information Architecture is potentially capable of increasing/reducing Digital Stress when browsing Digital Social Media. From this perspective, this research had the general objective: Analyze the influence of Information Architecture and the increase in Digital Stress situations in people in Digital Social Media. And as specific objectives: a) Develop a concept, characteristics and functions about Digital Stress in the context of Information Science; b) Analyze the Information Architecture and Signs of Digital Stress in Facebook, Instagram and TikTok Digital Social Media and c) Propose recommendations to reduce situations of Digital Stress in users of Digital Social Media. In relation to methodological aspects, it uses a qualitative approach and integrative literature review, with outlines in the quadripolar method, especially in aspects related to eidetic reduction and essential phenomenological elements about the concept, characteristics and functions of Digital Stress, in order to answer the 1st specific objective, based on the analysis of data collected in the CAPES portal databases: Web of Science (Clarivate Analytics), Scopus (Elsevier) and PsycINFO. Furthermore, the results of the concept construction, characteristics and functions of Digital Stress made it possible to contribute, through the use of a smartphone, in reply to the 2nd specific objective of this research, as well as enabling the repositioning of the Pervasive approach of Information Architecture to the Pervasive and ubiquitous Informational approach, suggesting, as one of the ways to face the digital stress dissipated on social networks, the elaboration of the model with five phases, which corresponds to the 3rd specific objective of this research: alert, resistance, innovative repulsion measures, exhaustion and combat measures, when this model integrated the navigation system, present in the proposed informational architectural environment. The study opens up a range of possibilities for complementary research, concerning the psychological impact resulting from the use of Digital Social Media, especially regarding Digital Stress, as well as mechanisms for promoting, preventing and recovering people's emotional balance.